Educational excellence and learner diversity : can the teacher achieve excellence in all students - Saheed Ahmad Rufai, (penerbit ukm, 2010)
The attainment of excellence is the ultimate goal of any systematic endeavour. Education is not an exception in this regard as the teacher’s effort in imparting knowledge to his students is expectedly intended to facilitate effective and meaningful learning. Yet the diverse socio-economic backgrounds, psychological orientations and even religious persuasions of the learner have significant roles to play in determining the success rate achievable in the teachinglearning process. Hence the question: can the teacher achieve excellence in all students, in the face of learner diversity? The purpose of this paper is to articulate the multidimensional nature of excellence in education and to identify diverse various strategies that are capable of aiding the attainment of excellence in learners, in the face of educational diversity. The significance of such an analysis lies in the fact that it provides a meaningful explanation on the growing concern over the possibility or otherwise of the teacher’s achievement of excellence in all his or her students. The paper is both critical and analytical in its method and relies on respected authorities in articulating the concept of diversity in education and its relationship with grading, educational accountability, and educational excellence. It concludes that excellence is somewhat synonymous with progress, success, achievement, distinction, victory, fulfillment,accomplishment and other words of similar nature, all of which should be regarded as relative in the face of learner diversity which, itself is a challenge to the success of the teacher’s efforts in the classroom